Legal and accounting aspects of the activities of non-profit (non-entrepreneurial) organizations - Pataraia, Lela (Business and Legislation, 2008)
The modern world is distinguished by the abundance of non-profit, non-governmental (non-profit) organizations, which are known as non-governmental, public or civil organizations. We encounter such organizations almost at every step - be it trade unions, associations, sports federations, public organizations working on various social issues (so-called welfare organizations), etc. Non-profit organizations play an important role in the formation and development of societies. The services provided by these organizations meet the needs of society that other sectors cannot or do not reach. Non-profit organizations are also distinguished by their elasticity - they successfully control individual areas, be it healthcare, environmental protection, culture, science, social security for orphans, the elderly, the disabled, the deaf and dumb and the blind, or others.